Echinococcus multilocularis inoculation induces NK cell functional decrease through high expression of NKG2A in C57BL/6 mice - Abulizi, Abuduaini (BMC Infect Dis, 2019)
BACKGROUND: Alveolar echinococcosis (AE) is caused by the larval stage of Echinococcus multilocularis (E. multilocularis), and considered as public health issue. Parasite-host immune interaction is pivotal during infection. As a subset of innate lymphoid cells, NK cells are known to play an important role during virus, bacteria, intra/extracellular parasitic infections and tumor progression. However, the possible role of NK cells in E. multilocularis infection in both human and murine is little known. Herein, the functional alteration of hepatic NK cells and their related molecules in E. multilocularis infected mice were studied. METHODS: 2000 protoscoleces (PSCs) were injected to C57BL/6 mice via the portal vein to establish secondary E. multilocularis infection. NK cells population and their related molecules (CD69, Ly49D, Ly49G2, Ly49H, Ly49I, NKG2A, NKG2D, granzyme B, IFN-γ, TNF-α) were assessed by using fluorescence-activated cell sorter (FACS) techniques and qRT-PCR. NK cell depletion was performed for further understanding the possible function of NK cells during infection. RESULTS: The total frequencies of NK cells and NK-derived IFN-γ production were significantly reduced at designated time points (2, 4, 12 weeks). The liver resident (CD49a(+)DX5(−)) NK cells are decreased at 4 weeks after inoculation and which is significantly lower than in control mice. Moreover, in vivo antibody-mediated NK cell depletion increased parasitic load and decreased peri-parasitic fibrosis. Expression of the inhibitory receptor NKG2A was negatively related to NK- derived IFN-γ secretion. CONCLUSIONS: Our study showed down regulates of NK cells and upper regulates of NKG2A expression on NK cells during E. multilocularis infection. Reduction of NK cell frequencies and increased NKG2A might result in low cytotoxic activity through decreased IFN-γ secretion in E. multilocularis infection. This result might be helpful to restore NK cell related immunity against E. multilocularis infection to treat alveolar echinococcosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12879-019-4417-1) contains supplementary material, which is available to authorized users.